Expanding the Fields of Use of Concretes Based on Sulfur Binder by Increasing Thermal Characteristics of Them - Ahmedov Islombek G’ulomjonovich; Kholmirzayev Sattor Abdujabborovich; Umarov Isroiljon Isoqjon o’g’li; Nuritdinov Jasurbek Davlatali o‘g‘li (PT. Antis International Publisher, 2024)
The article describes the results of the experiment on transferring sulfur binder-based concretes from the combustible group to the difficult combustible group in order to expand the use aspects.